Worker Flows and Wage Dynamics: Estimating Wage Growth without Composition Effects - Raquel Carrasco; J. Ignacio García-Pérez; Juan F. Jimeno (Institute of Labor Economics (IZA), 2020)
Wage dynamics is closely intertwined with job flows. However, composition effects associated to the different sizes and characteristics of workers entering/ exiting into/from employment that may blur the "true" underlying wage growth, are not typically accounted for. In this paper, we take these composition effects into consideration and compute wage growth in Spain during the 2006-2018 period after netting out the consequences of employment dynamics. Our results show that the "true" underlying wage growth in the Spanish economy during recessions (expansions) was, on average, significantly lower (higher) that the observed with raw data. This may help to explain some macro puzzles, such as the "vanishing" Phillips curve.
Keywords: J30; J31; J21; 330; wage growth; composition effects; selection bias